Addressing the Decline in Young Students’ Learning Motivation: Revitalizing Classical Guidance at Pesantren Kyai Syarifuddin Dalem Timur, Lumajang - Khoirah, Mutiatul (Risalatuna Journal of Pesantren Studies, 2024)
This study explores the implementation of classical guidance to improve the learning motivation of young students at Pondok Pesantren Kyai Syarifuddin Dalem Timur, Lumajang. Unlike most Islamic boarding schools that accept adolescents aged 13 and above, this pesantren accommodates elementary-aged students, which presents unique pedagogical challenges. A qualitative descriptive approach was adopted, involving observation, in-depth interviews, and documentation analysis. The results reveal that systematic classical guidance, which includes scheduled motivational sessions, reward systems, and intensive supervision, significantly enhanced students’ motivation, discipline, and participation in learning. Indicators such as punctual attendance, task completion, and classroom engagement improved markedly after the intervention. However, the implementation faced several challenges, including limited teaching creativity, difficult student behavior, and ineffective communication with parents. These were addressed through interactive learning strategies, media integration, and empathetic communication training for staff. The study concludes that classical guidance, when delivered in a structured and participatory manner, is a practical and effective approach to fostering learning motivation among young students in pesantren.